Epikarst - A Promising habitat Copepod fauna, its diversity and ecology. A case study from Slovenia (Europe) - Pipan, Tanja (Carsologica, 2005)
The book represents a detailed study of the fauna of drips and drip pools in six caves in Slovenia. Drips and drip pools are important because they are just about the only way of assessing the epikarst community. Using a special sampling device, it was possible to sample individual drips for extended periods of time. A total of 37 species of copepods were found in drips and drip pools. Significant differences in the fauna between drips and pools, presumably because of differential survival and reproduction in pools were found. Somewhat surprisingly it was found that the kind of pool, e.g., mud-bottomed compared to calcite bottomed, made little difference.